Al-Thaqāfah wa Taʿlīm al-Lughah al-ʿArabiyyah li al-Nāṭiqīn bi-Lughāt Ukhrā - Moh Ismail (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2014)
The teaching of Arabic, like the teaching of any other language, aims not merely to train learners to pronounce Arabic sounds, memorize vocabulary, or master grammatical structures; rather, it seeks broader and deeper educational objectives. Specialists in Arabic language education generally identify three fundamental competencies that should be achieved through Arabic language instruction: linguistic competence, communicative competence, and cultural competence. These three competencies represent the primary goals of second-language learning and should be developed in an integrated manner throughout the instructional process. Since language is the vessel of culture, it is difficult to learn a language without being exposed to the culture of its speakers, including their values, beliefs, lifestyles, and patterns of behavior. Following the revelation of the Qur’an and the mission of the Prophet Muhammad, Arabic culture became closely associated with Islamic civilization, and the Arabic language assumed a central role as the language of Islamic worship and cultural expression. Within the context of teaching Arabic as a second language, this close relationship between language and culture has raised important questions among scholars and educators, including which culture should be taught—Arab, Islamic, or national culture—how cultural content should be presented in second-language instruction, and whether Arabic culture can be integrated with learners’ local cultures. This article explores the relationship between culture and Arabic language teaching and discusses these key issues in order to provide a clearer understanding of the role of culture in teaching Arabic as a second language.